2012
DOI: 10.1165/rcmb.2011-0153oc
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Endothelial Cell Permeability by High and Low Doses of Oxidized 1-Palmitoyl-2-Arachidonyl-sn-Glycero-3-Phosphocholine

Abstract: The generation of phospholipid oxidation products in atherosclerosis, sepsis, and lung pathologies affects endothelial barrier function, which exerts significant consequences on disease outcomes in general. Our group previously showed that oxidized 1-palmitoyl-2-arachidonyl-sn-glycero-3-phosphocholine (OxPAPC) at low concentrations increases endothelial cell (EC) barrier function, but decreases it at higher concentrations. In this study, we determined the mechanisms responsible for the pulmonary endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…Interestingly, in OxPAPC-treated neutrophils stimulated with opsonized S. aureus, a significant increase in the amount of ROS was seen. Previous studies reported that OxPAPC has the potential to increase ROS release in endothelial cells via activating the NADPH oxidase (58,59). Moreover, Fc gamma receptor (Fc␄R) signaling is known to trigger ROS release (60).…”
Section: Figmentioning
confidence: 99%
“…Interestingly, in OxPAPC-treated neutrophils stimulated with opsonized S. aureus, a significant increase in the amount of ROS was seen. Previous studies reported that OxPAPC has the potential to increase ROS release in endothelial cells via activating the NADPH oxidase (58,59). Moreover, Fc gamma receptor (Fc␄R) signaling is known to trigger ROS release (60).…”
Section: Figmentioning
confidence: 99%
“…It has been reported that Ox-PL can interact with ECs, monocyte/macrophages, platelets and SMCs through acting on different receptors to stimulate various signaling pathways underlying AS [157]. High concentration of Ox-PLs can disrupt endothelial integrity and increase endothelial permeability [158]. Ox-PLs can also facilitate macrophage lipid accumulation and foam cell formation by upregulating CD36 expression [159].…”
Section: The Pro-atherogenic Effect Of Fasmentioning
confidence: 99%
“…However, even in HAEC, PEIPC at low concentrations decreases breakdown of the endothelial barrier (increased breakdown is seen in inflammation); whereas at higher concentrations PEIPC stimulates barrier breakdown. 25 In dendritic cells PEIPC strongly inhibits the pro-inflammatory action of bacterial lipids. 26, 27 While the effect of PEIPC is more complex, the effect of EI is mainly anti-inflammatory in both HAEC and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%